Alzheimer's disease risk variants modulate endophenotypes in mild cognitive impairment - Louwersheimer, Eva; Frölich, Lutz (Alzheimer's and dementia, 2016)
Introduction - We evaluated the effect of Alzheimer's disease (AD) susceptibility loci on endophenotypes closely related with AD pathology in patients with mild cognitive impairment (MCI). - Methods - We selected 1730 MCI patients from four independent data sets. Weighted polygenic risk scores (PGS) were constructed of 18 non-apolipoprotein E (APOE) AD risk variants. In addition, we determined APOE genotype. AD endophenotypes were cognitive decline over time and cerebrospinal fluid (CSF) biomarkers (aβ, tau, ptau). - Results - PGS was modestly associated with cognitive decline over time, as measured by mini-mental state examination (MMSE) (β ± SE:-0.24 ± 0.10; P = .012), and with CSF levels of tau and ptau (tau: 1.38 ± 0.36, P = 1.21 x 10-4; ptau: 1.40 ± 0.36, P = 1.02 x 10-4). - Discussion - In MCI, we observed a joint effect of AD susceptibility loci on nonamyloid endophenotypes, suggesting a link of these genetic loci with neuronal degeneration in general rather than with Alzheimer-related amyloid deposition.
Gesehen am 09.08.2019